2002
DOI: 10.1128/iai.70.9.4946-4954.2002
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Vaccination with Carrier Protein on Response to Meningococcal C Conjugate Vaccines and Value of Different Immunoassays as Predictors of Protection

Abstract: In order to plan for the wide-scale introduction of meningococcal C conjugate (MCC) vaccine for United Kingdom children up to 18 years old, phase II trials were undertaken to investigate whether there was any interaction between MCC vaccines conjugated to tetanus toxoid (TT) or a derivative of diphtheria toxin (CRM 197 ) and diphtheria-tetanus vaccines given for boosting at school entry or leaving. Children (n ‫؍‬ 1,766) received a diphtheria-tetanus booster either 1 month before, 1 month after, or concurrent… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
79
2

Year Published

2003
2003
2015
2015

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 86 publications
(84 citation statements)
references
References 17 publications
3
79
2
Order By: Relevance
“…The distributions of rSBA titers post-primary vaccination against MCC in infants, toddlers, and preschool children (Table 1) were taken from a series of studies (16,14,4) in which testing was carried out at the Manchester Public Health Laboratory by standardized rSBA methods (3). All the children received Meningitec, a cross-reactive mutant-based conjugate vaccine produced by Wyeth Lederle Vaccines (Pearl River, N.Y.).…”
Section: Methodsmentioning
confidence: 99%
“…The distributions of rSBA titers post-primary vaccination against MCC in infants, toddlers, and preschool children (Table 1) were taken from a series of studies (16,14,4) in which testing was carried out at the Manchester Public Health Laboratory by standardized rSBA methods (3). All the children received Meningitec, a cross-reactive mutant-based conjugate vaccine produced by Wyeth Lederle Vaccines (Pearl River, N.Y.).…”
Section: Methodsmentioning
confidence: 99%
“…It is therefore important that studies on concomitant use be performed in adolescents to ascertain the compatibility of new vaccines alongside Tdap. To date, two published studies have investigated the interaction between meningococcal C conjugate (MenC) vaccines and tetanus and reduced-antigen diphtheria (Td) boosters in adolescents 13 to 18 years old; these found no clinically relevant impact on the reactogenicity or immunogenicity of the MenC vaccines (4,21).…”
mentioning
confidence: 99%
“…Our results demonstrate that the current cohorts of children entering adolescence are unlikely to have protective levels of antibody, and thus, herd immunity may also start to wane. Furthermore, children in this study mainly received a MenC-CRM 197 conjugated vaccine, which was found to be the least immunogenic of the three licensed MenC conjugate vaccines (3,5). It was in wide use during the national immunization campaign, so these results could be generalized to a large group of United Kingdom adolescents.…”
Section: Discussionmentioning
confidence: 99%